The Influence of Imperfect Movie on Student Perceptions in Bandung City - Dwi Anggyan; Nala Nandana Undiana; Salsa Solli Nafsika (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Film is a medium that has an influence on the entire audience. The influence obtained through the film can be in the form of changes in mindset, behavior and everything related to human psychological aspects. In today's modern era, all social issues can be raised as a storytelling topic in a film, one of which is the issue of body shaming or demeaning behavior of others, the issue was later raised into a film entitled Imperfect which was released in 2019. In this study, researchers will analyze how the influence of the film Imperfect on the audience's perception that is devoted to students. The researcher uses quantitative research methods in the data collection process and is carried out by distributing questionnaires then the data obtained will be analyzed through several data tests, so that the results of this study can be achieved.